Comparison of the efficacy of 70% Trichloroacetic Acid versus Cryotherapy in the Treatment of Plantar Warts - Kausar, Sameena; Shazia; Mazhar, Hina; Saleem, Sumyra; Naveed, Tehseen; Irshad, Ommaya (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the efficacy of 70% Trichloroacetic acid and Cryotherapy as a treatment modality in the resolution of plantar warts. Methods: This quasi-experimental study was conducted in the Dermatology department of a care hospital, from September 2024 to February 2025. 70 patients visiting the outpatient department meeting the inclusion criteria were enrolled in the study after approval from the hospital ethical committee. Informed written consent was taken from participants, and they were allocated into two groups. Group A was treated with Cryotherapy every two weeks, and those in Group B received a 70% Trichloroacetic acid application every week. All patients were followed for 8 weeks in order to assess the efficacy and to monitor the side effects of treatment. Results: The mean age in the Cryotherapy group was 35.9 ± 9.16 years, and in the Trichloroacetic acid group was 33.67 ± 9.64 years. There were 44 (62.85%) male and 26 (37.14%) female participants in this study. Efficacy of therapy for plantar warts was observed in 14 (40%) patients in the 70% Trichloroacetic acid group, while in 9 (25.71%) patients in the Cryotherapy group, having a non-significant p value of 0.203. Conclusion: 70% Trichloroacetic acid is equally effective as compared to Cryotherapy in the treatment of plantar warts, and it may be considered as a suitable alternative therapeutic option due to its comparable efficacy, easy availability, cost-effectiveness, and tolerability. Keywords: Cryotherapy, Efficacy, Plantar Warts, Trichloroacetic Acid